The Effect Of Employee Engagement, Organizational Commitment And Compensation On Employee Performance At BSI Bank S. Parman Branch Office Medan - Ipil Candra; Alvin Fahlevi; M. Fauzan Azhmey (Journal of Innovative and Creativity, 2025)
This research was conducted at Bank BSI K antor C abang . S.Parman Medan with the aim of the research to determine the effect of work engagement, organizational commitment and compensation on employee performance. The population in this study were plantation employees who worked at Bank BSI K antor C abang S.Parman as many as 70 employees and sampling with saturated samples so that the number of samples was 70 respondents. The data source used primary data and data collection techniques using surveys, namely questionnaires. Data analysis techniques used classical assumption tests, hypothesis tests and multiple linear regression. Based on the results of the research conducted, it shows that work engagement, organizational commitment, and compensation partially and simultaneously have a significant effect on employee performance in carrying out their duties. There is a strong correlation between work engagement, organizational commitment, and compensation with employee performance. Employee performance in the company can be explained by work engagement, organizational commitment, and compensation by 56.2%, while the remaining 43.80% can be explained by other variables not examined.